Features of immune homeostasis disorders and their role in the pathogenesis of the development of adrenaline damage to the myocardium and experimental periodontitis - Ilyk, R.; Regeda, M.; Sushinsky, Y. (Journal of Education, Health and Sport, 2025)
Aim. The aim of the study was to determine the pathophysiological features of changes in humoral and cellular immunity and their role in the mechanisms of development of experimental periodontitis (EP) associated with adrenaline myocardial injury (AMI). Material and methods. Experimental studies were conducted on 63 white rats (males), which were divided into three groups: intact group (control), APM on the 1st, 3rd and 7th days; APM and EP on the 1st, 3rd and 7th days. Experimental periodontitis (EP) was reproduced by the method of Demkovich A.E., APM was reproduced by the method of Markova O.O. The content of T and B lymphocytes in the blood was determined by the method of Chernushenko K.F., CIC - by the method of Haskova V. Statistical analysis of digital results was performed by the Student method. Results. The results of the studies showed that under the conditions of APM development, there was a decrease in the level of T-lymphocytes and an increase in B-lymphocytes with a predominance on the 1st day of the experiment compared to the control, and under the conditions of comorbid pathology (APM and EP), suppression of cellular immunity was observed against the background of stimulation of humoral immunity with dominance on the 3rd and 7th days, which indicated significant violations of immune homeostasis indicators and their important role in the pathogenesis of the development of the indicated experimental disease models.